2015 IEEE 17th International Conference on High Performance Computing and Communications, 2015 IEEE 7th International Symposium 2015
DOI: 10.1109/hpcc-css-icess.2015.251
|View full text |Cite
|
Sign up to set email alerts
|

Offline Analysis of Independent Guarded Assertions in Automotive Integration Testing

Abstract: The size and complexity of software in automotive systems have increased steadily over the last decades. Modern vehicles typically contain numerous electrical control units (ECUs), and more and more features require real-time interaction between several dedicated ECUs (e.g., gearbox, brake and engine control units) in order to perform their tasks. Since system safety and reliability must not be adversely affected by this increase in complexity, proper quality assurance is a must. Such quality assurance is ofte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In automotive system testing, scenario-based testing is commonly used, where a scenario is typically a sequence of system events [19]. This typically results in hardcoded scripted test cases that are difficult to test for non-determinism [18] as well as for interactions among various configurations and signal combinations. The proposed independent guarded assertions [20] allow for parallel execution of test cases, with frequent evaluation of assertions that are not typically captured in requirements and thus allows for testing of functional interactions.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In automotive system testing, scenario-based testing is commonly used, where a scenario is typically a sequence of system events [19]. This typically results in hardcoded scripted test cases that are difficult to test for non-determinism [18] as well as for interactions among various configurations and signal combinations. The proposed independent guarded assertions [20] allow for parallel execution of test cases, with frequent evaluation of assertions that are not typically captured in requirements and thus allows for testing of functional interactions.…”
Section: Related Workmentioning
confidence: 99%
“…A more general in-depth review of passive testing methods can be found in [15]. In previous work on the SAGA approach, interviews with practitioners [16] have shown that passive testing using guarded assertions [14], [17], [18] seems to contribute to small tests, preferably one test per requirement, which should facilitate both alignment as well as traceability.…”
Section: Introductionmentioning
confidence: 99%